Changing hospitals, choosing chemotherapy and deciding you've made the right choice: Understanding the role of online support groups in different health decision-making activities. Issue 5 (May 2017) - Sillence, Elizabeth; Bussey, Lauren
Highlights: OSGs prompt decision making and allow people to evaluate and confirm decisions. Experience narratives valued by people contemplating health service use change. Interactivity of OSGs is a key factor in usefulness as decision resource. OSGs support a wider range of health decision-making than simply treatment choices. Abstract: Objective: To investigate the ways in which people use online support groups (OSGs) in relation to their health decision-making and to identify the key features of the resource that support those activities. Method: Eighteen participants who used OSGs for a range of health conditions participated in qualitative study in which they were interviewed about their experiences of using OSGs in relation to decision-making. Exploration of their experiences was supported by discussion of illustrative quotes. Results: Across the health conditions OSGs supported two main decision-making activities: (i) prompting decision making and (ii) evaluating and confirming decisions already made. Depending on the activity, participants valued information about the process, the experience and the outcome of patient narratives. The importance of forum interactivity was highlighted in relation to advice-seeking and the selection of relevant personal experiences. Conclusion: People use OSGs in different ways to support their health related decision-making valuing the different content types of the narratives and the interactivity provided by the resource. Practice implications: Engaging with OSGs helps people in a number of different ways in relation to decision-making. However, it only forms one part of people's decision-making strategies and appropriate resources should be signposted where possible.